Life cycle analysis (LCA) of residential ground source heat pump systems: A comparative analysis of energy efficiency in New Jersey. (October 2021) - Smith, Meghann; Bevacqua, Anthony; Tembe, Sheryl; Lal, Pankaj
Highlights: Ground Source Heat Pumps can decrease the environmental impact of residential heating and cooling. The PJM electricity generating fuel mix allows for improved sustainability metrics in New Jersey. Ground Source Heat Pump system use allows for decreased greenhouse gas emissions. Ground Source Heat Pumps outperform other methods of space heating and cooling. Abstract: Developing clean energy policy supported by science-based research is essential for mitigating the hazards and risks associated with climate change. This study aims to explore ground source heat pump (GSHP) systems, an underutilized energy efficiency technology, as a means to promote emission reductions in the buildings sector. GSHP systems have the capacity to decrease the environmental impact of building space heating and cooling needs through fossil fuel displacement and higher energy efficiencies than baseline technologies. Although the benefits and engineering applications of this technology are established, it has not been adopted at scale, thus limiting potential emission reductions. Furthermore, energy economics can vary significantly across geographies which makes quantifying benefits of mitigation action challenging in regions with diverse electricity generator types and building heating fuels. This study uses life cycle analysis (LCA) to evaluate mid- and long-term sustainability metric impacts of GSHP systems operating in New Jersey, US, to assess the technology's effectiveness while operating within the state's electricity generating fuel mix. Results show that the state is a suitable location for residential GSHP systems, and that an electricity generation fuel mix with increased use of renewable energy sources would enhance the technology's efficiency and decrease associated emissions even further. In addition, we compared GSHP technology to that of other common space heating/cooling methods and found that use of GSHP systems in conjunction with electric-based heating/cooling provides a substantial improvement in terms of environmental emissions. When compared to oil and gas-based heating, GSHP systems provided some improvement on mid-point impact factors and considerable improvement on end-point impact factors, most notably the economic improvement associated with decreasing dependence on fossil fuels. These findings suggest that GSHP systems should be considered for reducing emissions and end-use energy consumption and support new clean energy policies in the state.